Adjuvant medical therapy in cervical dystonia after deep brain stimulation: A retrospective analysis - Martinez-Nunez, Alfonso E.; Sidiropoulos, Christos; Wall, Julia; Schwalb, Jason; Air, Ellen; LeWitt, Peter; Bulica, Bisena; Kaminski, Patricia; Patel, Neepa (Frontiers in Neurology, 2022)
Background There is limited information on optimization of symptomatic management of cervical dystonia (CD) after implantation of pallidal deep brain stimulation (DBS). Objectives To describe the long-term, “real-world” management of CD patients after DBS implantation and the role of reintroduction of pharmacologic and botulinum toxin (BoNT) therapy. Methods A retrospective analysis of patients with focal cervical or segmental craniocervical dystonia implanted with DBS was conducted. Results Nine patients were identified with a mean follow-up of 41.7 ± 15.7 months. All patients continued adjuvant oral medication(s) to optimize symptom control post-operatively. Three stopped BoNT and four reduced BoNT dose by an average of 22%. All patients remained on at least one medication used to treat dystonia post-operatively. Conclusion Optimal symptom control was achieved with DBS combined with either BoNT and/or medication. We suggest utilization of adjuvant therapies such as BoNT and/or medications if DBS monotherapy does not achieve optimal symptom control.